Organic matter inoculated with diazotrophic bacterium Beijerinckia indica and Cunninghamella elegans fungus containing chitosan on banana “Williams” in field - Newton Pereira Stamford; Emmanuella Vila Nova Silva; Wagner da Silva Oliveira; Marta Cristina Freitas da Silva; Marllon dos Santos Martins; Vinicius Santos Gomes da Silva (Acta Scientiarum. Agronomy, 2017)
The production of biofertilizers from rocks increases nutrients for plant nutrition without environmental pollution. The aim of this study was to evaluate the effectiveness of biofertilizers from phosphate and potassium rocks mixed with organic matter (earthworm compound) inoculated with free living diazotrophic bacteria (NFB 10001) and Cunninghamella elegans (fungus with chitosan) on yield, characteristics, and nutrient uptake of banana (cv. Williams), and attributes of a Red Yellow Argisoil of the rainforest Zone of Pernambuco, Brazil. The experimental design included two biofertilizers: (a) PK rock biofertilizers plus organic matter (NPKB) and (b) bioprotector (NPKP) applied at 50, 100 and 150% of the recommended rate for banana, which were compared with soluble mineral fertilizers (NPKF) applied at the recommended rate, and earthworm compound (20 ton ha-1). The best results of the plant parameters were obtained with NPKB and NPKP applied at the highest rates (150% RR). A normal yield was produced when NPKB and NPKP were applied at the highest rates and NPKF at the recommended rate. The available P and K in the soil showed a significant fertilization effect, especially when NPKB and NPKP were applied at the highest rates. The biofertilizer and bioprotector may be alternatives to mineral soluble fertilizers.